The Role of Local Government In The Development of Human Resources For Songkok Recca MSME Artisans As Local Cultural Products In Bone Regency South Sulawesi Province - Hamid, Hendrawati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The economy of Indonesian society is currently largely controlled by micro, small and medium enterprises (MSMEs), therefore these micro enterprises must be developed by the Indonesian government. The purpose of this study is to analyze the efforts made by local governments in developing the quality of human resources for songkok recca MSME artisans. Various problems faced in the development of artisan human resources such as production technology that is still very simple because all production processes are carried out by hand (hand made), business management that is not well organized (aspects of HR management, production management, financial management, marketing management), and inadequate business capital. The research method used is qualitative descriptive, data collection is carried out through semi-structured interviews, observation, focus group discussion (FGD), and literature studies. Respondents were determined by purposive sampling consisting of, Head of Service and Head of Division from related agencies, sub-districts, traditional leaders, and craftsmen. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. To measure the development of artisan human resources that have been implemented by local governments, it is measured using four indicators, namely, HR management, production management, financial management, and marketing management. The results showed that the four indicators analyzed have been running according to the rules but some have not, but the results havehad enough impact on increasing the economic activity of craftsmen, because the profits obtained depend on the quality of the production produced, the better the quality of the products produced, the higher the price so that the profits obtained are also higher.